Long-term occurrence of Trypanosoma congolense resistant to diminazene, isometamidium and homidium in cattle at Ghibe, Ethiopia - Mulugeta, W.; Wilkes, J.; Mulatu, W.; Majiwa, Phelix A.O.; Masake, R.; Peregrine, A.S. (Elsevier, 1997)
Ten trypanosome isolates were collected at random from cattle at Ghibe, Ethiopia, in February 1993 and all shown to be savannah-type Trypanosoma congolense. When inoculated into naive Boran (Bos indicus) calves, all 10 isolates were resistant to diminazene aceturate (Berenil), isometamidium chloride (Samorin) and homidium chloride (Novidium) at doses of 7.0 mg/kg body weight (b.w.), 0.5 mg/kg b.w. and 1.0 mg/kg b.w., respectively. In order to determine whether this multiple-drug resistance as expressed by individual trypanosomes, clones were derived from two of the isolates and characterised in mice for their sensitivity to the three compounds; by comparison to drug-sensitive populations, the two clones expressed high levels of reistance to all 3 trypanocides. In experiments to characterise the uptake kinetics of (14C)-Samorin, the maximal rates of uptake (V max) for 4 Ghibe isolates ranged from 9.2 to 15.0 ng/10(8) trypanosomes/min. In contrast, V max for the isometamidium-sensitive clone T. congolense IL 1180 was 86.7 (+ or -) 8.6 ng/10(8) trypanosomes/min. Lastly, molecular karyotypes were determined for eight isolates; seven different chromosome profiles were observed. These data indicate that in February 1993 there was a high prevalence of drug-resistant trypanosome populations with different chromosome profiles in cattle at Ghibe. Since a similar situation existed at the same site in July 1989, this suggests that drug-resistance phenotype of trypanosomes at Ghibe had not altered over a 4 year period.